Die Bedeutung Johannes Pauls II. in der Auseinandersetzung zwischen Theologie und Naturwissenschaften - Sławomir Śledziewski (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
One of the characteristics of the teaching of Pope John Paul II is his approach to the subject of faith and reason, which have played a central role in the development of civilization. They work best when they mutually challenge one another to look farther, to probe more deeply, in quest of truth. Hostility between faith and reason is not accepted because both have their source in God. But when both work together, the human person has the chance of discovering the full truth about himself, the world and God. The author of this article argues that a large number of papal documents and pronouncements of Pope John Paul II show his contribution towards the bringing together of natural sciences and theology. This is also a challenge for those who continue this effort.